John L. Stoddard's Lectures, Vol. 10 (of 10) : Southern California; Grand Cañon of the Colorado River; Yellowstone National Park - Stoddard, John L. (John Lawson), 1850-1931 (Salt Lake City, UT : Project Gutenberg, 2005)
"John L. Stoddard's Lectures, Vol. 10 (of 10)" by John L. Stoddard is a travelogue written in the late 19th century. This work encompasses Stoddard's explorations of various notable locations in the United States, with particular focuses on Southern California, the Grand Canyon of the Colorado River, and Yellowstone National Park, showcasing the beauty and diversity of theseregions. The book employs vivid descriptions and personal reflections to immerse readers in the experiences of a traveler navigating through these landmarks. The opening of the volume depicts Stoddard's journey into Southern California, emphasizing the region's harsh yet fascinating landscapes. He vividly describes the desolation of the surrounding deserts, transitioning into the lushness found in areas influenced by irrigation. He contrasts the various cities and cultures encountered, from the remnants of Native American life to the vibrant contemporary communities, showcasing how these factors contribute to the unique character of Southern California. The text captures not only the physical journey but also the diverse human experiences existing within these evolving spaces, providing a reflective lens on the changes occurring in the American West during this period. (This is an automatically generated summary.)
Release date is 2005-04-02
E-text prepared by Juliet Sutherland, Sandra Brown, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Grand Canyon (Ariz.) -- Description and travel; California, Southern -- Description and travel; Yellowstone National Park -- Description and travel